On the search for the two poles of the $$Ξ (1820)$$ Ξ ( 1820 ) in the $$ψ (3686) → \bar{Ξ }^+ \bar{K}^0 Σ ^{*-}(π ^- Λ )$$ ψ ( 3686 ) → Ξ ¯ + K ¯ 0 Σ ∗ - ( π - Λ ) decay - Man-Yu Duan; Jing Song; Wei-Hong Liang; E. Oset (European Physical Journal C: Particles and Fields)
Abstract We propose the reaction $$ψ (3686) → \bar{Ξ }^+ \bar{K}^0 Σ ^{*-}$$ ψ ( 3686 ) → Ξ ¯ + K ¯ 0 Σ ∗ - , with the $$Σ ^{*-}$$ Σ ∗ - decaying to $$π ^- Λ $$ π - Λ in order to show evidence for the existence of two $$Ξ (1820)$$ Ξ ( 1820 ) states, one around 1824 MeV and narrow, and another one around 1875 MeV and wide. The phase space for $$\bar{K}^0 Σ ^{*-}$$ K ¯ 0 Σ ∗ - production reduces the effect of the lower mass resonance, magnifying the effect of the higher mass resonance that shows clearly over the phase space. The estimated rate of the production is bigger than the one of the $$ψ (3686) → \bar{Ξ }^+ K^- Λ $$ ψ ( 3686 ) → Ξ ¯ + K - Λ reaction, where a clear peak for $$Ξ (1820)$$ Ξ ( 1820 ) was observed by the BESIII collaboration, what makes the Beijing facility ideal to carry out the reaction proposed.